Digital Transformation Leadership in Elementary School Management: Evidence from a Digital School Transformation Program - Isep Djuanda; Sri Andriyani (Journal of Educational Management Research, 2026)
This study aims to examine the role of digital transformation leadership in strengthening elementary school management and improving educational quality. The research employed a qualitative approach using a systematic literature review combined with a case study to explore leadership practices, challenges, and strategies for implementing digital transformation in primary education. The findings reveal that effective digital transformation leadership depends on the integration of a clear strategic vision, digital competencies, and an adaptive organizational culture. School leaders play a pivotal role in promoting technology adoption, enhancing teachers’ digital capacity, fostering collaboration, and establishing a sustainable digital learning ecosystem. Furthermore, continuous professional development and stakeholder engagement are essential for ensuring the successful implementation of digital initiatives. The study implies that educational institutions should develop a contextual digital leadership model that prioritizes human resource development as the foundation for sustainable digital transformation and improved educational management. Such a model can support schools in responding effectively to technological change while enhancing organizational performance and learning quality.